Seberapa Besar Pengaruh Metode Pembelajaran Talking Stick Pada Hasil Belajar Siswa SD/MI? - Rizky, Muhammad; Jadidah, Ines Tasya; Eprilia, Winda; Shawmi, Ayu Nur; Saputra, Agra Dwi (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2024)
The acquisition of learning outcomes of Indonesian students in PISA in 2019 occupies the bottom 6 out of 77 countries, the latest PISA results in 2023 also show aligned results where they occupy the bottom 15 of 88 countries where the subject matter begins to emerge from the elementary / MI level. This study aims to examine how much influence the talking stick method has on students' learning outcomes, especially at the elementary / MI level. The research method used is a quantitative meta-analysis type with a comparison of group contrast design. The population in the study was 191 articles from the Google Scholar, DOAJ, and Research Gate databases. The sampling technique is an inclusion criterion. The number of samples used is 10 articles that fit the criteria. The effect of all studies was 1,633 for studies with a sample of < 30 of 1,576 and a sample of > 30 of 1,727 and a P-value hypothesis test result of 0.001. Based on this, the author concludes that the talking stick learning method has a  significant effect and has a huge effect on influencing the learning outcomes of elementary / MI students, especially used when the number of students is> 30. So that this method can be a solution to overcoming the problem of obtaining student learning outcomes in Indonesia.